KRT8 Serves as a Novel Biomarker for LUAD and Promotes Metastasis and EMT via NF-κB Signaling - Chen, Hao; Chen, Xiaobin; Pan, Bo; Zheng, Chutian; Hong, Liangjie; Han, Weili (Frontiers in Oncology, 2022)
Keratin8 (KRT8) is the major component of the intermediate filament cytoskeleton and aberrant expression in multiple tumors. However, the role of KRT8 in lung adenocarcinoma (LUAD) remains unclear. In the present study, KRT8 expression was found to be upregulated along with prognosis and metastasis in LUAD. Kaplan-Meier analysis presented that the 5-year OS and DSS rates were significantly better among patients with low KRT8 expression compared to those with high expression. Correlation analysis showed that KRT8 expression was significantly associated with gender (P =0.027), advanced T stage (P =0.001), advanced N stage (P =0.048), and advanced pathologic stage (P =0.025). Univariate Cox analysis demonstrated that KRT8 was a predictor of OS (HR 1.526; 95% CI 1.141-2.040; P = 0.004) and DSS (HR 1.625; 95% CI 1.123-2.353; P = 0.010) in the TCGA database. Importantly, downregulation of KRT8 obviously suppressed cell proliferation, cell migration, invasion and EMT as well as induced cell apoptosis, while overexpression of KRT8 promoted cell migration, invasion and EMT in vitro and in vivo. Mechanistically, KRT8 knockdown significantly inhibited NF-κB signaling, while KRT8 overexpression activated NF-κB signaling via p65 nuclear translocation. Overall, our results indicated that KRT8 could regulate lung carcinogenesis and may serve as a potential target for antineoplastic therapies.